Apigenin Combined With Gefitinib Blocks Autophagy Flux and Induces Apoptotic Cell Death Through Inhibition of HIF-1α, c-Myc, p-EGFR, and Glucose Metabolism in EGFR L858R+T790M-Mutated H1975 Cells - Chen, ZiSheng; Tian, Dongbo; Liao, Xiaowen; Zhang, Yifei; Xiao, Jinghua; Chen, Weiping; Liu, Qingxia; Chen, Yun; Li, Dongmin; Zhu, Lianyu; Cai, Shaoxi (Frontiers in Pharmacology, 2019)
Cancer cells are characterized by abnormally increased glucose uptake and active bio-energy and biosynthesis to support the proliferation, metastasis and drug resistant survival. We examined the therapeutic value of the combination of apigenin (a naturalsmall-molecule inhibitor of Glut1belonging to the flavonoid family) and gefitinib on epidermal growth factor receptor (EGFR)-resistant mutant non-small cell lung cancer, to notably damage glucose utilization and thus suppress cell growth and malignant behavior. Here, we demonstrate that apigenin combined with gefitinib inhibits multiple oncogenic drivers such as c-Myc, HIF-1α and EGFR, reduces Gluts and MCT1 protein expression and inactivates the 5' adenosine monophosphate-activated protein kinase (AMPK) signaling which regulates glucose uptake and maintains energy metabolism, leading to impaired energy utilization in EGFR L858R-T790M mutated H1975 lung cancer cells. H1975 cells exhibit dysregulated metabolism and apoptotic cell death following treatment with apigenin + gefitinib. Therefore, the combined apigenin + gefitinib treatment presents an attractive strategy as alternative treatment for the acquired resistance to EGFR-TKIs in NSCLC.